Efficient Synthesis of the Pentasaccharide Repeating Unit of the O-Antigenic Polysaccharide of Escherichia coli O166 Strain - Si, Anshupriya; Misra, Anup Kumar (Synthesis, 2015)
An efficient strategy has been developed for the synthesis of the pentasaccharide repeating unit of the cell-wall polysaccharide of Escherichia coli O166 strain through sequential stereoselective glycosylations of monosaccharide intermediates. All the glycosylation steps were high-yielding with high stereoselectivities.
Keywords: carbohydrates; glycosylations; glycosides; stereoselectivity; oligosaccharides